Novo deposit?rio sylvestre do Schizotrypanum cruzi (Chagas, 1900): a ir?ra, tayra barbara (L) - Ferreira, Leoberto de Castro (MS/SVS/Instituto Evandro Chagas, 2018)
Publicado originalmente em Brasil M?dico, v. 52, n. 52, p. 1159-1161, dez. 1938